Relation with postpartum maternal morbidity of different types of anesthesia in preeclamptic patients - Hasan Ulubaşoğlu; Kadir Bakay; Davut Güven (Taylor & Francis Group, 2018)
Objective: The aim of this study is to investigate the effect of different anesthesia types administered to patients with preeclampsia on postoperative maternal morbidities. Methods: Medical records of pregnant women complicated with preeclampsia delivered by cesarean from January 2010 to December 2016 in our clinic were retrospectively reviewed. Results: There was not a statistically significant difference between patients receiving spinal anesthesia and general anesthesia in terms of additional parenteral analgesic requirement at postoperative period (p = 0.520). The length of stay in hospital and δHb (preoperative hemoglobin value minus postoperative hemoglobin value) were not different between spinal anesthesia and general anesthesia groups (p = 0.140 and 0.648, respectively). The rate of postoperative antihypertensive medication requirement was statistically significant in patients with severe preeclampsia who underwent general anesthesia (p = 0.009, x2 = 6.867, odds ratios = 4.276 (1.531-11.942)). The time passing to reach the first normal blood pressure level in patients with severe preeclampsia was 11.95 ± 9.11 h in patients with spinal anesthesia, 10.55 ± 4.95 h in patients with general anesthesia, and the difference was not statistically significant (p = 0.504). Conclusion: The need for antihypertensive medication is greater in patients with severe preeclampsia receiving general anesthesia. There is a need for comprehensive, prospective, and randomized controlled trials to establish the relationship between postpartum morbidity and the different types of anesthesia.